Analisis Persepsi Orang Dengan HIV (ODHIV) Terhadap Risiko Penularan COVID-19 Di Kota Padang Tahun 2021 - M Angga Mahalta; Rika Sabri; Mahathir Mahathir (Universitas Batanghari Jambi, 2021)
People living with HIV (PLHIV) are group that have a weak immune system. In addition to HIV, the world is also facing the COVID-19 pandemic. The number of COVID-19 cases every time continues to increase until the current third wave. People living with HIV are a group that needs more attention in dealing with this pandemic. One way to initiate preventive action is to look at the perception of the protected aggregate. A person's level of alertness to an event can be seen from how they see the object to be perceived. Exploring the perception of people living with HIV can provide an overview of how they view and deal with COVID-19. This research use qualitative research methods with a phenomenological approach. The selection of participants used purposive sampling technique. The data analysis technique used the Colaizzi technique. There were ten themes found in this study, the views of people living with HIV on COVID-19, feelings of people living with HIV in dealing with COVID-19, awareness of differences in immune conditions and being a vulnerable group, belief in ARVs strengthening the body's immune system, views of people living with HIV on the risk of transmitting COVID-19, PLHIV's views on health protocols, activities that strengthen the immune system, social support, adaptation of Puskesmas services during a pandemic, PLHIV's perception of vaccination. The results of the study show that people living with HIV are a vulnerable population that needs more attention, especially during this COVID-19 pandemic. Cooperation between health care workers and policy makers should be increased to reach and protect the population of PLWHIV.